Effects of prenatal exposure to air particulate matter on the risk of preterm birth and roles of maternal and cord blood LINE-1 methylation: A birth cohort study in Guangzhou, China. (December 2019) - Liu, Xin; Ye, Yufeng; Chen, Yi; Li, Xiaona; Feng, Baixiang; Cao, Ganxiang; Xiao, Jianpeng; Zeng, Weilin; Li, Xing; Sun, Jiufeng; Ning, Dan; Yang, Yi; et al.
Abstract: Background: Epidemiological studies have found that increased risk of preterm birth (PTB) is associated with higher prenatal exposure to PM10 and PM2.5, but few studies have been conducted to assess the impacts of extremely fine particulate matter (PM1 ) which may have more toxic effects than other types of ambient particulate air pollution (PM). Several studies have separately investigated the associations between DNA methylation and PTB risk and PM. Maternal LINE-1 methylation level negatively correlated with prenatal exposure to PM and risk of PTB. A comprehensive picture is lacking regarding the associations between prenatal exposure to PM, LINE-1 methylation, and risk of PTB. Objectives: This study aimed to estimate the effects of exposure to ambient PM (PM10, PM2.5, and PM1 ) of different sizes during pregnancy on risk of PTB, identify susceptible exposure windows, and illustrate the roles of LINE-1 methylation in the associations between PM and PTB risk. Methods: The Birth Cohort Study on Prenatal Environments and Offspring Health (PEOH) has been ongoing since 2016 in Guangzhou, China. A total of 4928 pregnant women were recruited during early pregnancy, and 4278 (86.8%) were successfully followed-up. Each individual weekly exposure to PM10 and PM2.5 from 3 months before pregnancy to childbirth was assessed using a spatiotemporal land use regression model, and the weekly PM1 exposure was estimated by employing a generalized additive model. Maternal and cord blood LINE-1 methylation levels (%5mC) were tested using bisulfite-PCR pyrosequencing. A distributed lag nonlinear model incorporated with a Cox proportional hazard model was applied to assess the effect of weekly-specific maternal PM exposure on PTB risk, and a multiple-linear regression model was employed to investigate the associations between PM exposure and LINE-1 methylation levels of maternal and cord bloods. We also assessed the associations between LINE-1 methylation levels and PTB risk by using a logistic regression model. Results: The risk of PTB was positively associated with PM2.5 and PM1 concentrations during the 12th to 20th gestational weeks, and the strongest association was in the fourth quartile (Q4 ) versus the first quartile (Q1 ) and observed during the 16th gestational week (PM2.5 : harzard ratio [HR] = 1.18, 95%CI: 1.04–1.35, IQR = 11.94 μg/m 3 . PM1 : HR = 1.20, 95%CI: 1.03–1.39, IQR = 11.36 μg/m 3 ). We observed significantly negative associations of PM10 ( β = −0.51%5mC per 10 μg/m 3, P = 0.014), PM2.5 ( β = −0.66%5mC per 10 μg/m 3, P = 0.032) and PM1 ( β = −0.67%5mC per 10 μg/m 3, P = 0.032) concentrations with cord blood LINE-1 methylation levels, and a negative association between PM1 concentration and maternal LINE-1 methylation level ( β = −0.86%5mC per 10 μg/m 3, P = 0.034). Conclusion: Higher prenatal exposure to PM1 and PM2.5 during the 12th to 20th gestational weeks was associated with increased risk of PTB. Maternal and fetal LINE-1 methylation alternation might be an underlying mechanism of PM that increasing the risk of PTB. Highlights: Preterm birth (PTB) risk was positively associated with prenatal exposure to PM2.5 and PM1, and a slightly greater effect was found for PM1 compared with PM2.5 . Gestational weeks 12 to 20 might be the critical window with the peak effect in the 16th week. Fetal LINE-1 methylation was simultaneously associated with prenatal exposure to ambient particulate air pollution (PM) and PTB risk, indicating that LINE-1 methylation alternation might be an underlying mechanism of PM increasing PTB risk. However, the roles of maternal LINE-1 methylation may differ compared with their infants.